THE CASE BASED REASONING METHOD TO DIAGNOSE THE STRESS LEVEL OF STUDENTS FINAL SEMESTER - M Reza Redo Islami; M Adie Syaputra; Aditya Fikri Haikal (International Research on Big-Data and Computer Technology: I-Robot, 2020)
CBR (Case-Based Reasoning) is a method that can provide a solution to a new previous case based on the closeness between the old case and the new problem case, on the knowledge base with new cases from what happened, case-based reasoning has the advantage that this method can be used in building a system that is based or comes directly from the knowledge of an expert, the source of this expert's knowledge is by obtaining from the collection of handling cases of old symptoms from an expert, so that the case-based reasoning method can solve a new problem so that with these stages the application of the method CBR can later produce an application that results in a determination of the level of stress symptoms, therefore the researcher tries to apply the method into a stress level diagnostic application which is expected to be able to help students find out the level of stress they are experiencing which aims to make the research results this can be applied to an application